2021
DOI: 10.1007/s10900-021-01017-9
|View full text |Cite
|
Sign up to set email alerts
|

Parental Perspectives on Immunizations: Impact of the COVID-19 Pandemic on Childhood Vaccine Hesitancy

Abstract: Childhood vaccine hesitancy has been studied extensively before the COVID-19 pandemic. The pandemic presented new barriers to pediatric vaccinations. Furthermore, the development of COVID-19 vaccines has complicated factors underlying vaccine hesitancy. We performed a cross-sectional mobile phone-based survey at Children's Hospital Los Angeles querying parents regarding perspectives on vaccines before and during the pandemic. Our primary aim was to understand the impact of the pandemic on routine childhood vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
62
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 20 publications
7
62
1
Order By: Relevance
“…This result was contrary to various studies showing that parents with low education and income were less likely to intend to vaccinate their children [18]. The higher the income, the greater the probability of accepting vaccination against COVID -19 [40,41]. However, this might be explained by persons with economic insecurity having been more vulnerable to COVID-19 in the region [42].…”
Section: Discussioncontrasting
confidence: 79%
“…This result was contrary to various studies showing that parents with low education and income were less likely to intend to vaccinate their children [18]. The higher the income, the greater the probability of accepting vaccination against COVID -19 [40,41]. However, this might be explained by persons with economic insecurity having been more vulnerable to COVID-19 in the region [42].…”
Section: Discussioncontrasting
confidence: 79%
“…Several socio-demographic characteristics that we found to be associated with parents' intention to vaccinate their children are consistent with previous studies. For example, these previous studies found that significantly higher proportions of males [22][23][24], older parents [21], higher educational level [23,25] and higher income [25,26] exhibited higher intentions to vaccinate children against COVID-19.…”
Section: Discussionmentioning
confidence: 93%
“…Of note, amongst our cohort of healthcare providers, just 3% of respondents reported prior vaccine behavior of delaying their children's immunizations, which is low compared to the general population [27]. As the world moves toward childhood immunizations for COVID-19, the relationship between vaccine hesitancy for oneself vs. for one's child is a topic that should be explored in future studies, particularly among minority groups who may be at higher risk [28].…”
Section: Discussionmentioning
confidence: 85%